Formation of beryllium-hydrogen ions in chemical sputtering from 20 to 420eV. (January 2020) - Ballauf, Lorenz; Hechenberger, Faro; Stadlmayr, Reinhard; Dittmar, Timo; Daxner, Matthias; Zöttl, Samuel; Aumayr, Friedrich; Herman, Zdenek; Scheier, Paul
Highlights: A Be surface is sputtered by D2 + with impact energies from 20 to 420 eV, different temperatures, flux and adsorbate coverage. All secondary ion species are resolved by time-of-flight mass spectrometry. Two seperate reaction channels forming beryllium-hydrogen ions have been resolved. There is a direct reaction of the projectile with the surface, yielding a high ratio BeD + /Be + ≈ 3 at only 20 eV D2 + impact. BeH + can also be created from hydrogen-containing surface adsorbate, most efficiently from water. There is no evidence found, that the projectile reaction relies on prior D implantation in the bulk Be. Abstract: The formation of BeD + in collisions of deuterium molecular ions with a beryllium surface at hyperthermal energies is investigated, using a purpose-built tandem mass spectrometer setup, "SurfTOF". In the manifold of products, hydrogen-containing molecules are of special interest in fusion devices. Our experiments show, that they can be formed in nearly all conditions comparable to plasma and wall temperature, with two mechanisms involved: First, BeD + is formed directly in a reaction of the D2 + projectiles with the Be surface, which is the main aspect of this work. There was no evidence found, that this particular mechanism relies on D implanted in the bulk Be. BeD2 + was not detected. The second reaction pathway produces BeH + . It is efficiently formed when H2 O molecules are adsorbed on the surface, much less abundant for hydrocarbon adsorbates. The yield of Be +, BeH + and BeD + products, is measured as a function of several parameters: Scanning the impact energy from 20 to 426 eV reveals that the molecular BeD + is preferably produced at low energies. At 20 eV, its abundance is three times higher than that of pure Be + . When the surface temperature is raised from 298 to 673 K, sputtering yields increase two orders of magnitude for both, Be + and BeD + .